LEKSIKOGRAFSKI PRISTOPI K OSNOVNEMU BESEDIŠČU (Filološke pripombe, 2019)
The article discusses the concept of basic vocabulary. It aims to demonstrate the scope of basic vocabulary and the methods of determining it. Although its range may vary from 600 to 15,000, it usually contains ca. 2,000 words. The selection of basic vocabulary is based on statistical text analyses which yield the frequency of text elements. According to this frequency, the key words of corpuses representative of a given language are chosen. However, as the majority of the most frequent words of a language are grammatical words, the frequency list should be supplemented by other selection methods. Thus, various researchers have maintained that beside the frequency list another one should be defined by means of surveys or the lexicogra- pher’s choice. Apart from the frequency list the basic vocabulary hence consists of the so-called “available vocabulary,” a list of thematic words referring to extradis- coursive reality. The list of the most frequent as well as the most necessary words of a given linguistic community, obtained by this method, is most commonly used in lexicography of learner’s dictionaries. Some of these dictionaries, both mono- and bilingual, are reviewed in the final section of the article.